Analysis of Moral Values in the Song of Onogu Omasiö by Daniel Folala Zalukhu - Gea, Boy Berkat Iman; Mastawati Ndruru; Lestari Waruwu; Iman Sudi Zega (Jurnal Sastra Indonesia, 2024)
This research aims to describe the moral values in the song "Onogu Omasi'ö" by Daniel Folala Zalukhu. This research is a qualitative descriptive study. The data source in this research is the lyrics or verses of the song "Onogu Omasi'ö" by Daniel Folala Zalukhu. The variables in this research are the moral values  in the Nias song "Onogu Omasi'ö" by Daniel Folala Zalukhu. Data collection can be done in various ways according to the data required; the data collected is primary. The data collection techniques in this research are observation and documentation; the researcher makes observations by observing, listening, and listening carefully and carefully to each lyric of the song "Onogu Omasi'ö" by Daniel Folala Zalukhu, then documenting the results of the observation in the form of a video link or song lyrics " Onogu Omasi'ö” by Daniel Folala Zalukhu and its translation. As a result of the research, researchers found aspects of four moral values, including (1) the moral value of a human relationship with God as much as one data, namely blessing with a percentage of 7%; (2) four data sets of human relationships with themselves consisting of honesty, reminiscing and hope with a percentage of 27%; (3) nine data sets of human relations with others consisting of advice, messages and promises with a percentage of 60%; and (4) the relationship between humans and the environment is one piece of data, namely the workplace environment with a percentage of 7%.